Towards Exploring the Benefits of Augmented Reality for Patient Support During Radiation Oncology Interventions. Issue 3 (4th May 2021) - Martin-Gomez, A.; Hill, C.; Lin, H.Y.; Fotouhi, J.; Han-Oh, S.; Wang, K.K.-H.; Navab, N.; Narang, A.K.
ABSTRACT: Traditionally, patient education has been limited to verbal exchanges between providers and patients, along with paper handouts that summarise relevant information. While such exchanges are a natural step in educating patients, they are limited for several reasons, including the lack of time that provider teams are afforded, and the inherent challenge of communicating nuanced concepts related to complex medical procedures. A clear example of this is radiation oncology, in which traditional routes of patient education may not satisfy the patient's needs. Although existing work has demonstrated the ability of audio-visual systems to improve patient engagement during medical procedures, the integration of emerging technologies such as Augmented Reality (AR) remains largely untapped. In this work, we propose an innovative proof-of-concept AR system as a first step towards exploring the benefits of using this technology during radiotherapy sessions. Our concept uses an AR headset to provide visual feedback of the patient's respiratory trace presented using two different forms: (i) a bi-dimensional graph and (ii) a game-based user interface. Moreover, we explore how interactive environments have the potential to contribute to better user experience and improve engagement, and discuss different challenges that must be addressed to deploy this technology to radiation treatment sessions.